1992
DOI: 10.1056/nejm199205143262003
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetogenic Effect of Glucagon-like Peptide-1 (7–36)amide in Normal Subjects and Patients with Diabetes Mellitus

Abstract: GLIP has an antidiabetogenic effect, and it may therefore be useful in the treatment of patients with NIDDM:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
534
3
6

Year Published

1997
1997
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 863 publications
(556 citation statements)
references
References 38 publications
13
534
3
6
Order By: Relevance
“…Several studies have indicated that GLP-1 might have an insulin-independent effect on glucose homeostasis [26][27][28][29][30][31][32], while other researchers suggested that GLP-1 did not acutely affect glucose metabolism independently of insulin [33][34][35][36][37]. These conflicting results may be a consequence of the large variability in the model and methods used: healthy vs diabetic, diabetic hyperglycaemic vs diabetic maintained euglycaemic, clamp vs IVGTT etc.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that GLP-1 might have an insulin-independent effect on glucose homeostasis [26][27][28][29][30][31][32], while other researchers suggested that GLP-1 did not acutely affect glucose metabolism independently of insulin [33][34][35][36][37]. These conflicting results may be a consequence of the large variability in the model and methods used: healthy vs diabetic, diabetic hyperglycaemic vs diabetic maintained euglycaemic, clamp vs IVGTT etc.…”
Section: Discussionmentioning
confidence: 99%
“…Using complementary pharmacological, biochemical and molecular biology approaches, we provide evidence that GLP-1, a gluco-incretin hormone under consideration for diabetes treatment [25,26], prevents glucose-and palmitate-induced apoptosis in the beta cell by a mechanism involving PKB and its downstream target NF-κB.…”
Section: Discussionmentioning
confidence: 99%
“…Glucagon-like peptide-1-(7-36) amide (GLP-1), a potent gluco-incretin hormone [21,22,23] secreted by the intestinal L-cells in response to fat meals and carbohydrates [24], is a potentially important drug in the treatment of Type 2 diabetes in view of its ability to improve insulin secretion in subjects with impaired glucose tolerance and Type 2 diabetes mellitus [25,26]. Through its ability to stimulate insulin gene expression and proinsulin biosynthesis [27] GLP-1 is also an insulinotropic agent.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, results from in vivo studies have been less consistent. GLP-1 (7-36) has been reported to increase glucose uptake during hyperglycaemia and hyperinsulinaemia in diabetic rats [17], pancreatectomized dogs [18] and in Type I (insulin-dependent) diabetic patients [19,20]. In contrast, GLP-1 (7-36) has been reported to have no effect on the insulin action in non-diabetic human subjects [21] GLP-1 (7-36) is actively being evaluated as a therapy for diabetes mellitus.…”
mentioning
confidence: 99%
“…A positive but small effect on insulin action has most consistently been observed in severely insulin deficient animals or Type I diabetic patients [18,20]. The methods used to assess insulin action also have differed ranging from clamps, to frequently sampled intravenous glucose tolerance tests to prandial infusions of glucose [17,18,19,20,21,22,23]. We were intrigued by the possibility that the pattern of degradation of GLP-1 (7-36) also might have influenced the results of these studies.…”
mentioning
confidence: 99%